PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER SISWA DI ERA INDUSTRI 4.0 - Augusni Hanna Niwati Telaumbanua (Institut Agama Kristen Negeri (IAKN) Ambon, 2020)
Abstract: In this paper the authors reveal the role of Christian Religious Education in shaping the character of students in the era of the industrial revolution 4.0, becoming a new